Understanding the common agricultural policy - Hill, Berkeley (Earthscan food and agriculture, 2012)
Most of the written material on the Common Agricultural Policy (CAP) is about the details of the day. This work offers an understanding of why the policies are as they are, how they attempt to tackle the problems faced in the European Union and the degree of success they achieve, and the prospects for change